Studies of inclusions and their host diamonds from the Gahcho Kué mine, Canada ... - Siva-Jothy, William (University of Alberta Library, 2020)
Gahcho Kué is a diamond mine in the Northwest Territories of Canada that opened in 2016. This is the first study into the morphology, N systematics, and stable isotope (C and N) composition of the Gahcho Kué diamonds, and the mineral chemistry of the associated inclusions. The resulting data are used to provide insight into the poorly understood and characterised mantle of the Southern Slave Craton, and the mantle conditions that gave rise to the diamond association within the area. Results from 88 inclusion-bearing diamond samples show that diamond formation beneath the Gahcho Kué mine occurred primarily in depleted peridotitic mantle (84%), with some minor contribution from eclogitic (15%) and websteritic (1%) mantle. Assessment by geothermobarometry revealed relatively cold lithospheric conditions compared to other diamondiferous localities within the Slave craton. The trace element chemistry of associated garnets revealed the standard sinusoidal pattern of depletion and re-enrichment by metasomatic ...